Acceptability and feasibility of a social entrepreneurship testing model to promote HIV self‐testing and linkage to care among men who have sex with men. Issue 5 (7th September 2016) - Zhong, F; Tang, W; Cheng, W; Lin, P; Wu, Q; Cai, Y; Tang, S; Fan, L; Zhao, Y; Chen, X; Mao, J; Meng, G; et al.
Abstract : Objectives: HIV self‐testing (HIVST) offers an opportunity to increase HIV testing among people not reached by facility‐based services. However, the promotion of HIVST is limited as a consequence of insufficient community engagement. We built a social entrepreneurship testing (SET) model to promote HIVST linkage to care among Chinese men who have sex with men (MSM) in Guangzhou. Methods: The SET model includes a few key steps. Each participant first completed an online survey, and paid a US$23 (refundable) deposit to receive an HIVST kit and a syphilis self‐testing (SST) kit. After the testing, the results were sent to the platform by the participants and interpreted by Center for Disease Control and Prevention (CDC) staff. Meanwhile, the deposit was returned to each participant. Finally, the Community based organizations (CBO) contacted the participants to provide counselling services, confirmation testing and linkage to care. Results: During April−June 2015, a total of 198 MSM completed a preliminary survey and purchased self‐testing kits. The majority were aged < 34 years (84.4%) and met partners online (93.1%). In addition, 68.9% of participants had ever been tested for HIV, and 19.5% had ever performed HIVST. Overall, feedback was received from 192 participants (97.0%). Of these participants, 14 people did not use the kits; among those who did use the kits, the HIV and syphilis prevalences were 4.5% (eight of 178) and 3.7% (six of 178), respectively. All of the screened HIV‐positive individuals sought further confirmation testing and were linked to care. Conclusions: Using an online SET model to promote HIV and syphilis self‐testing among Chinese MSM is acceptable and feasible, and this model adds a new testing platform to the current testing service system.